Spatial distribution trend of plankton in Sungai Pulai Estuary, the straits of Johor, Malaysia - Kassim, Zaleha; Yunus, Kamaruzzaman; Khan Chowdhury, Ahmed Jalal; Jaafar, Ili Nabilah; Nordin, Nur Suhaila; Wan Ahmad, Wan Muhamad Amir; Ismail, Ahmad; John, Akbar (Penerbit UKM, 2015)
A spatial distribution study was carried out to investigate the influence of some environmental factors to planktons using collected samples from the Sungai Pulai estuary, near to the Singapore boarder. Six stations chosen for the field sampling were Port Tanjung Pelepas (S1), Tanjung Bin Charcoal Plant (S2), seagrasses of Pulau Merambong (S4) and Second-Link Bridge (S5) and mangrove areas (S3, S6). There is no significant difference of phytoplankton abundance (p>0.05) between stations. Instead, it differs significantly at the level of p<0.05; p= 0.0001 (Two tailed, t=14.10 df=34) between sampling session. In contrast, there is a significant difference of zooplankton abundance (p<0.05) in the sampling stations (χ2 = 17.3,(5)), but there is no significant difference (p>0.05; p=0.8966) between the sampling session (Two tailed, t=0.1310, df=34). Biplot analysis shows that most species are associated with the stations except for Protoperidinium sp., Lithodesmia sp. and Alexendrium sp. Copepod species including Microcalanus sp., Calanus sp. and Temora sp. are associated with S5. Paracalanus sp., Euterpina sp., Tigriopus sp., Oithona sp. and Pseudocalanus sp. are associated with S1, S2 and S4. The planktons are correlated with the temperature (Pearson’s correlation, r2=-0.897) and salinity (Pearson’s correlation, r2=0.9416) in March but no correlation is found in November sampling session. The results indicated the important role of certain environmental factors, namely the salinity and temperature to the distribution of the planktons in Sungai Pulai estuary.